Beyond the Chinese connection : contemporary Afro-Asian cultural production - Anderson, Crystal S. (UPCC book collections on Project MUSE., 2013)
In Beyond The Chinese Connection, Crystal S. Anderson explores the cultural and political exchanges between African Americans, Asian Americans, and Asians over the last four decades. To do so, Anderson examines such cultural productions as novels (Frank Chin's Gunga Din Highway [1999], Ishmael Reed's Japanese By Spring [1992], and Paul Beatty's The White Boy Shuffle [1996]); films (Rush Hour 2 [2001], Unleashed [2005], and The Matrix trilogy [1999-2003],) and Japanese animation (Samurai Champloo [2004]), all of which feature cross-cultural conversations. In exploring the ways in which writers and artists use this transferral, the author traces and tests the limits of how Afro-Asian cultural production interrogates conceptions of race, ethnic identity, politics, and transnational exchange.